PENGARUH EARNING PER SHARE DAN RETURN ON ASSET TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Gusti Ayu Mahanavami (Forum Manajemen, 2014)
Themanufacturingcompanyisoneofthecompaniesthatrequireahuge capitaltocover itsoperatingcosts. To meet the company’s manufacturingcapital into the stock market. The aim of this study was to determine the effect ofEPS and ROA on stock prices on companies listed in Indonesia Stock Exchangeeither simultaneously or partially. Data used in this study are: qualitative data andquantitative data, the data sources are secondary data. The method of data collectionwas done by the study documentation, whereas analytical techniques used are: TestClassical Assumption, multiple linear regression and hypothesistesting.The results of this study are Earning per Share (EPS) has a positive and significantimpact on stock prices so that the hypothesis is accepted. Retun on Assets (ROA) hasno significant positive effect on stock prices so that the hypothesis is rejected. Earning per Share (EPS) and Retun on Assets (ROA) together have a positive and significant impact on stock prices so that the hypothesis is accepted. As for the advice given isthat investors should pay attention to the EPS of a company, with the intention as amaterial consideration in making investment decisions in the stock market. Investorsshould consider the ROA despite having no significant influence on the developmentof the stock because ROA is often used to measure the efficiency of the use of assetsin a company.